2017
DOI: 10.1016/j.cdtm.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Current progress and outcomes of clinical trials on using epidermal growth factor receptor‐tyrosine kinase inhibitor therapy in non‐small cell lung cancer patients with brain metastases

Abstract: Non-small cell lung cancer (NSCLC) continues to be one of the major causes of cancer-related deaths worldwide, and brain metastases are the major cause of death in NSCLC patients. With recent advances in understanding the underlying molecular mechanism of NSCLC development and progression, mutations in epidermal growth factor receptor (EGFR) have been recognized as a key predictor of therapeutic sensitivity to EGFR tyrosine kinase inhibitors (TKIs). Using EGFR-TKI alone or in combination with standard treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Recently, TKIs-based chemotherapy has been applied as a standard adjunctive treatment strategy in advanced NSCLC patients after surgical resection (Gainor et al , 2017; Kong et al , 2017; Prabhu and Devaraj, 2017). The research on lncRNA and the gefitinib resistance of NSCLC cells has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TKIs-based chemotherapy has been applied as a standard adjunctive treatment strategy in advanced NSCLC patients after surgical resection (Gainor et al , 2017; Kong et al , 2017; Prabhu and Devaraj, 2017). The research on lncRNA and the gefitinib resistance of NSCLC cells has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a large survey from Chinese oncologists, the participants were unanimous in the view that radiotherapy (RT) plus TKIs were the preferred regimen for EGFRm NSCLC patients with BM when neurological symptoms presented (Yu et al 2022 ). The synergistic effects between EGFR-TKIs and RT have been proved in previous studies (Zeng et al 2015 ; Kong et al 2017 ). The disruption of RT to BBB increases the TKIs permeability, and TKIs lower the radiation resistance of overexpressed EGFR wild-type cells while elevating EGFR-mutant cells’ sensitivity to RT (Kong et al 2017 ; Khalifa et al 2016 ).…”
Section: Introductionmentioning
confidence: 57%
“…The synergistic effects between EGFR-TKIs and RT have been proved in previous studies (Zeng et al 2015 ; Kong et al 2017 ). The disruption of RT to BBB increases the TKIs permeability, and TKIs lower the radiation resistance of overexpressed EGFR wild-type cells while elevating EGFR-mutant cells’ sensitivity to RT (Kong et al 2017 ; Khalifa et al 2016 ). The clinical value of LT plus EGFR-TKIs for BM patients remains controversial.…”
Section: Introductionmentioning
confidence: 57%
“…Taken together, these results thus suggest that CP-673451 treatment could hold great promise as part of a novel therapeutic strategy against GBM. CP-673451 is a low molecular weight kinase inhibitor (molecular weight = 417.52) [ 26 ] with the potential capacity to diffuse freely through the BBB, although further in vitro and in vivo studies are certainly needed in order to measure the BBB permeability of this compound and whether it reaches the tumour-site at a physiologically relevant dose [ 43 , 44 ]. As mentioned above, inducing tumour cell differentiation, even partially, could make cancer growth more manageable and consecutively an ‘easier’ target for more conventional strategies, including surgery and chemotherapies.…”
Section: Discussionmentioning
confidence: 99%